2014
DOI: 10.1371/journal.pone.0090470
|View full text |Cite|
|
Sign up to set email alerts
|

Portuguese Community Pharmacists' Attitudes to and Knowledge of Antibiotic Misuse: Questionnaire Development and Reliability

Abstract: ObjectiveTo develop and evaluate the reliability of a self-administered questionnaire designed to assess the attitudes and knowledge of community pharmacists in Portugal about microbial resistance and the antibiotic dispensing process.MethodsThis study was divided into the following three stages: (1) design of the questionnaire, which included a literature review and a qualitative study with focus-group sessions; (2) assessment of face and content validity, using a panel of experts and a pre-test of community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
2
9
0
1
Order By: Relevance
“…A p<0.001 gave statistical significance. These results are similar to the results reported by other researchers 13,16,23,28,29,30 . Inappropriate use of antibiotics is well known to be one of the leading factors that cause antibiotic resistance 1,19 .…”
Section: Knowledge Of Pharmacists On Antibiotic Resistancesupporting
confidence: 93%
See 3 more Smart Citations
“…A p<0.001 gave statistical significance. These results are similar to the results reported by other researchers 13,16,23,28,29,30 . Inappropriate use of antibiotics is well known to be one of the leading factors that cause antibiotic resistance 1,19 .…”
Section: Knowledge Of Pharmacists On Antibiotic Resistancesupporting
confidence: 93%
“…Therefore, our study indicated that pharmacists working at the University Teaching Hospital have adequate knowledge, positive attitude, and good practices towards antibiotic resistance. These findings are in tandem with other results found in other studies 22,27,28,29 . Additionally, to fight AMR, pharmacists need to have adequate knowledge, positive attitudes, and good practices towards antibiotic use resistance.…”
Section: Practices Of Pharmacists On Antibioticsupporting
confidence: 92%
See 2 more Smart Citations
“…We are aware that published studies have assessed community pharmacists' attitudes towards antibiotic dispensing, microbial resistance and their misuse, knowledge and attitudes towards URTIs as well as dispensing antibiotics without a prescription (3,9,(26)(27)(28). However, we believe this is one of the first studies to comprehensively test pharmacists' knowledge regarding all aspects of antibiotic use across key domains, particularly important in countries with high rates of self-purchasing.…”
Section: Discussionmentioning
confidence: 99%